The Effect of Insulin Resistance on Prognosis of Non-Diabetic Patients Who Underwent Percutaneous Coronary Intervention - Yun, Kyeong Ho (The Korean Academy of Medical Sciences, 2006)
Insulin resistance is an important risk factor for coronary artery disease. However, there has been no data regarding its clinical effect on the outcomes of percutaneous coronary intervention (PCI) in non-diabetic patients. We analyzed 98 non-diabetic consecutive patients (59±11.5 yr, male:female=63:35) who underwent elective coronary angiography. The patients were divided into two groups: Group I (n=71; the value of HOMA-IR [homeostasis model assessment of insulin resistance] <2.6) and Group II (n=27; the value of HOMA-IR ≥2.6). In-hospital and 30-day major adverse cardiac events (MACE) were compared between the two groups. The concentrations of fasting insulin and triglyceride were significantly higher in Group II than in Group I. Significant correlations were observed between the value of HOMA-IR and body mass index (r=0.489, p<0.001), levels of total cholesterol (r=0.204, p=0.045), triglyceride (r=0.334, p=0.001) and apolipoprotein B (r=0.212, p=0.038). PCI was performed in 59 patients (60.2%). In-hospital and 30-day MACE were higher in Group II than Group I (2.4% vs. 27.8%, p=0.008; 2.4% vs. 27.8%, p=0.008). Multivariate analysis revealed that the value of HOMA-IR ≥2.6 was an independent predictor of MACE. Increased HOMA-IR level is an important prognostic indicator in non-diabetic patients underwent PCI.